Comparison of Dietary Supplement Intake between Healthy Individuals and Osteoporosis Patients in Gorgan, Iran - Mehrdad Aghaei; Samira Eshghinia; Sima Seddighi; Nafiseh Abdollahi; Fatemeh Mohammadzadeh; Maryam Shafigh; Saeed Amirkhanlou; Gholareza Veghari (Golestan University Of Medical Sciences, 2017)
Introduction: Osteoporosis is a common disease in Iran, which is associated with insufficient intake of vitamin D and calcium. Therefore, this study aimed to compare consumption of dietary supplements between healthy individuals and patients with osteoporosis referred to bone densitometry centers in Gorgan, north of Iran. Materials and Methods: This case-control study was conducted on women aged over 55 years who were at least 5 years postmenopausal. Overall, two groups of 130 subjects were enrolled via convenience sampling at 95% confidence interval. The subjects were divided into two groups of healthy individuals and patients with osteoporosis using Hologic QDR 4500 Elite Bone Densitometers and T-scores (-2.5: osteoporosis, above 1: normal). Anthropometric measurements (height, weight and waist circumference), and amount of dietary intake of calcium, vitamin D, vitamin E and multivitamins supplements were recorded by trained experts. Data collected were analyzed using SPSS software (version 16). Results: Healthy subjects consumed significantly higher amount of calcium supplement (18.5%) compared to subjects with osteoporosis (P = 0.001). Intake of vitamin D supplement was significantly higher (23.3%) in healthy subjects compared to patients (P = 0.003). Intake of vitamin E supplement and multivitamin was slightly higher in healthy subjects, but the difference was not statistically significant. Conclusions: At least half and two-thirds of individuals aged over 55 years take vitamin D and calcium supplements, respectively. Intake of calcium and vitamin D is significantly higher in healthy individuals compared to those with osteoporosis.